Embeddedness of Mathematics e-Assessment and Attitudes Affecting Adoption - Casey, Deirdre; Crowley, Julie (MSOR Connections, 2019)
The Numbas e-assessment system was first introduced to Cork Institute of Technology (CIT) in 2014. It has been implemented in several modules and is used regularly by a number of Lecturers. The aim of this case study was to investigate how embedded Numbas is in the Mathematics department in CIT and to examine the perceptions of the lecturing staff which have led to their individual adoptions of the Numbas e-assessment tool. The results of a survey of lecturers within the department show that the use of Numbas is common and varied and that Lecturers’ attitudes towards Numbas are positive. Several themes arose around ways to increase or improve the use of Numbas including the need for ongoing training and ideas for the broadening of use. Lessons learned could be applied to advancing the integration of Numbas in Cork Institute of Technology but may also be of use to others hoping to increase adoption of e-assessment in Mathematics within their institutions.